The expression can be written as:
(2x + 5) - 3
or:
5 + (2x - 3)
________________________
and simplified to: "2x + 2" .
_________________________
Answer:
<u>A</u>
Step-by-step explanation:
Taking c = 1 :
- x² + 2x + 1
- x² + x + x + 1
- x(x + 1) + 1(x + 1)
- (x + 1)(x + 1)
- (x + 1)² ⇒ Perfect square trinomial
Answer:
the first one would be 12 square feet
the second one would be 2961$
and the third one would be 125%
Step-by-step explanation:
i took the test
Answer:
Jaylen's conclusion is a valid conclusion because it is logical
Step-by-step explanation:
Jaylen's conclusion is a valid conclusion because it is logical. Regardless of not having all the necessary information needed to prove that the number of dogs is the sole main cause for an increase in cleaner usage she can still conclude this. Since dogs naturally bring in dirt from outside and make messes, and since Jaylene notices that families that are known to have more dogs are buying more floor cleaner then she can logically come to this conclusion.
Answer:
![x^2 + 4x + y^2 +8y = 0](https://tex.z-dn.net/?f=x%5E2%20%2B%204x%20%2B%20y%5E2%20%2B8y%20%20%3D%20%200)
Step-by-step explanation:
Given
![A = (-1,-2)](https://tex.z-dn.net/?f=A%20%3D%20%28-1%2C-2%29)
![B = (2,4)](https://tex.z-dn.net/?f=B%20%3D%20%282%2C4%29)
![AP:BP = 1 : 2](https://tex.z-dn.net/?f=AP%3ABP%20%3D%201%20%3A%202)
Required
The locus of P
![AP:BP = 1 : 2](https://tex.z-dn.net/?f=AP%3ABP%20%3D%201%20%3A%202)
Express as fraction
![\frac{AP}{BP} = \frac{1}{2}](https://tex.z-dn.net/?f=%5Cfrac%7BAP%7D%7BBP%7D%20%3D%20%5Cfrac%7B1%7D%7B2%7D)
Cross multiply
![2AP = BP](https://tex.z-dn.net/?f=2AP%20%3D%20BP)
Calculate AP and BP using the following distance formula:
![d = \sqrt{(x - x_1)^2 + (y - y_1)^2}](https://tex.z-dn.net/?f=d%20%3D%20%5Csqrt%7B%28x%20-%20x_1%29%5E2%20%2B%20%28y%20-%20y_1%29%5E2%7D)
So, we have:
![2 * \sqrt{(x - -1)^2 + (y - -2)^2} = \sqrt{(x - 2)^2 + (y - 4)^2}](https://tex.z-dn.net/?f=2%20%2A%20%5Csqrt%7B%28x%20-%20-1%29%5E2%20%2B%20%28y%20-%20-2%29%5E2%7D%20%3D%20%5Csqrt%7B%28x%20-%202%29%5E2%20%2B%20%28y%20-%204%29%5E2%7D)
![2 * \sqrt{(x +1)^2 + (y +2)^2} = \sqrt{(x - 2)^2 + (y - 4)^2}](https://tex.z-dn.net/?f=2%20%2A%20%5Csqrt%7B%28x%20%2B1%29%5E2%20%2B%20%28y%20%2B2%29%5E2%7D%20%3D%20%5Csqrt%7B%28x%20-%202%29%5E2%20%2B%20%28y%20-%204%29%5E2%7D)
Take square of both sides
![4 * [(x +1)^2 + (y +2)^2] = (x - 2)^2 + (y - 4)^2](https://tex.z-dn.net/?f=4%20%2A%20%5B%28x%20%2B1%29%5E2%20%2B%20%28y%20%2B2%29%5E2%5D%20%3D%20%28x%20-%202%29%5E2%20%2B%20%28y%20-%204%29%5E2)
Evaluate all squares
![4 * [x^2 + 2x + 1 + y^2 +4y + 4] = x^2 - 4x + 4 + y^2 - 8y + 16](https://tex.z-dn.net/?f=4%20%2A%20%5Bx%5E2%20%2B%202x%20%2B%201%20%2B%20y%5E2%20%2B4y%20%2B%204%5D%20%3D%20x%5E2%20-%204x%20%2B%204%20%2B%20y%5E2%20-%208y%20%2B%2016)
Collect and evaluate like terms
![4 * [x^2 + 2x + y^2 +4y + 5] = x^2 - 4x + y^2 - 8y + 20](https://tex.z-dn.net/?f=4%20%2A%20%5Bx%5E2%20%2B%202x%20%2B%20y%5E2%20%2B4y%20%2B%205%5D%20%3D%20x%5E2%20-%204x%20%2B%20y%5E2%20-%208y%20%2B%2020)
Open brackets
![4x^2 + 8x + 4y^2 +16y + 20 = x^2 - 4x + y^2 - 8y + 20](https://tex.z-dn.net/?f=4x%5E2%20%2B%208x%20%2B%204y%5E2%20%2B16y%20%2B%2020%20%3D%20x%5E2%20-%204x%20%2B%20y%5E2%20-%208y%20%2B%2020)
Collect like terms
![4x^2 - x^2 + 8x + 4x + 4y^2 -y^2 +16y + 8y + 20 - 20 = 0](https://tex.z-dn.net/?f=4x%5E2%20-%20x%5E2%20%2B%208x%20%2B%204x%20%2B%204y%5E2%20-y%5E2%20%2B16y%20%2B%208y%20%20%2B%2020%20-%2020%20%3D%20%200)
![3x^2 + 12x + 3y^2 +24y = 0](https://tex.z-dn.net/?f=3x%5E2%20%2B%2012x%20%2B%203y%5E2%20%2B24y%20%20%3D%20%200)
Divide through by 3
![x^2 + 4x + y^2 +8y = 0](https://tex.z-dn.net/?f=x%5E2%20%2B%204x%20%2B%20y%5E2%20%2B8y%20%20%3D%20%200)